ZNF804A genetic variation (rs1344706) affects brain grey but not white matter in schizophrenia and healthy subjects. Issue 1 (20th May 2014) - Nenadic, I.; Maitra, R.; Basmanav, F. B.; Schultz, C. C.; Lorenz, C.; Schachtzabel, C.; Smesny, S.; Nöthen, M. M.; Cichon, S.; Reichenbach, J. R.; Sauer, H.; Schlösser, R. G. M.; et al.
Abstract : Background: Genetic variation in the gene encoding ZNF804A, a risk gene for schizophrenia, has been shown to affect brain functional endophenotypes of the disorder, while studies of white matter structure have been inconclusive. Method: We analysed effects of ZNF804A single nucleotide polymorphism rs1344706 on grey and white matter using voxel-based morphometry (VBM) in high-resolution T1-weighted magnetic resonance imaging scans of 62 schizophrenia patients and 54 matched healthy controls. Results: We found a significant ( p  < 0.05, family-wise error corrected for multiple comparisons) interaction effect of diagnostic group x genotype for local grey matter in the left orbitofrontal and right and left lateral temporal cortices, where patients and controls showed diverging effects of genotype. Analysing the groups separately (at p  < 0.001, uncorrected), variation in rs1344706 showed effects on brain structure within the schizophrenia patients in several areas including the left and right inferior temporal, right supramarginal/superior temporal, right and left inferior frontal, left frontopolar, right and left dorsolateral/ventrolateral prefrontal cortices, and the right thalamus, as well as effects within the healthy controls in left lateral temporal, right anterior insula and left orbitofrontal cortical areas. We did not find effects of genotype of regional white matter in either of the two cohorts. Conclusions: Our findings demonstrate effects of ZNF804A genetic variation on brain structure, with diverging regional effects in schizophrenia patients and healthy controls in frontal and temporal brain areas. These effects, however, might be dependent on the impact of other (genetic or non-genetic) disease factors.